Antibacterial Activity and Cytotoxic Effect of Pelargonium peltatum (Geranium) against Streptococcus mutans and Streptococcus sanguinis - Samantha Coronado-López; Stefany Caballero-García; Miguel Angel Aguilar-Luis; Fernando Mazulis; Juana del Valle-Mendoza (Hindawi Limited, 2018)
Objective. To evaluate the in vitro antibacterial and cytotoxic properties of the methanolic extract of Pelargonium peltatum (geranium) against Streptococcus mutans (ATCC 25175) and Streptococcus sanguinis (ATCC 10556). Methods. Three extracts of P. peltatum were prepared using the leaf, stem, and root. Nine independent assays were prepared for each type of extract with chlorhexidine at 0.12% as the positive control. The agar diffusion method was performed to determine the antibacterial properties of each extract. The minimum inhibitory concentration (MIC) was determined using the microdilution method, and the cytotoxicity was analyzed by means of the MTT reduction test using a MDCK cell line. Results. The root extract had the highest antibacterial effect with a mean result of (27.68 ± 0.97) mm and (30.80 ± 0.55) mm against S. mutans and S. sanguinis, respectively. The minimum inhibitory concentration for the leaf and root extracts was 250 mg/mL for S. mutans and 125 mg/mL for S. sanguinis. Cytotoxicity assays showed that both extracts had a low cytotoxicity at high concentrations. The cellular viability was highest for the root extract at 95.3% followed by the stem extract at 80.8% and finally the leaf extract with 75.4%. Conclusions. These findings show the antibacterial properties of the methanolic extracts of P. pelargonium against S. mutans and S. sanguinis. These extracts were not cytotoxic at high concentrations.